A comparison of estrus synchronization with Syncro-Mate-B® to natural service - Middleton, C.; Brink, T.; Kiracofe, G.; Brethour, J.; Negus, R. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Conception rates and subsequent calving dates were compared between cows synchronized with Syncro-Mate-B® and inseminated by appointment and nonsynchronized cows bred by natural service. Average conception date was seven days earlier in the synchronized cows.
Keywords: Beef; Estrus; Synchronization